JURIDICAL REVIEW OF THE IMPLEMENTATION OF RELIGIOUS COURT DECISIONS REGARDING FATHER'S RESPONSIBILITY FOR CHILD CARE COSTS (HADHANAH) AFTER DIVORCE " - A Rahim; Andi Sugiati; Rismawati Rismawati (Journal Indonesia Law and Policy Review, 2020)
Marriage is a natural requirement of life whose purpose is, among other things, to obtain offspring, in order to carry on a kind life. The feeling of wanting to live together should be prepared carefully, because to create a harmonious, prosperous and happy household is not an easy thing. Therefore, it is highly recommended to be more careful in choosing a mate, namely by taking into account all the factors that support the preservation of a reciprocal husband and wife relationship so that in this togetherness can get peace in the household. method used in this research is to use a normative juridical approach. The juridical approach that uses secondary data sources is used to analyze various laws and regulations such as Law Number 1 of 1974, Government Regulation Number 9 of 1975, Compilation of Islamic Law, decisions of the Bantaeng Religious Court, Bantaeng Regency Number 107 / Pdt.G / 2014, Number 261 / Pdt.G / 2014 and Number 40 / Pdt.G / 2015 relating to childcare costs, fiqh books and Islamic law, as well as articles that have correlation and are relevant to the issues. The result showed that Consideration of Religious Court judge Bantaeng, Bantaeng in deciding a case divorce relating to child maintenance costs based on considerations. legal (a) The relevant Islamic law and regulations governing the cost of caring for children. (b)considerations Other, are the non-legal considerations or social economic conditions of the parties. (c) The amount of childcare costs depends very much on the condition income of the father's real. So, there is no uniformity regarding the amount costs of child care in the case of hadhanah